Effectiveness of Medicinal Plants for Glycaemic Control in Type 2 Diabetes: An Overview of Meta-Analyses of Clinical Trials - Willcox, Merlin L.; Elugbaju, Christina; Al-Anbaki, Marwah; Lown, Mark; Graz, Bertrand (Frontiers in Pharmacology, 2021)
AIMS: To rank the effectiveness of medicinal plants for glycaemic control in Type 2 Diabetes (T2DM) METHODS: MEDLINE, EMBASE, CINAHL and Cochrane Central were searched in October 2020. We included meta-analyses of randomised controlled clinical trials measuring the effectiveness of medicinal plants on HbA1c and/or Fasting Plasma Glucose (FPG) in patients with T2DM. RESULTS: 256 meta-analyses reported the effects of 18 plant-based remedies. Fenugreek seeds and Aloe vera leaf gel, Psyllium fibre and Fenugreek seeds had the largest effects on HbA1c: mean difference –1.16%, [95% CI –1.23, –1.09] and –0.99% [95% CI –1.75, –0.23], -0.97% [95% CI -1.94, -0.01] and -0.85% [95% CI -1.49, -0.22] respectively. Fourive other remedies reduced HbA1c by at least 0.5%: Psyllium fiber, Nigella sativa, Astragalus membranaceus, and the traditional Chinese formulae Jinqi Jiangtang and Gegen Qinlian. No serious adverse effects were reported. Several other phytoherbal medicines significantly reduced FPG. Tea and tea extracts (Camellia sinensis) were ineffective. However, in some trials duration of follow-up was insufficient to measure the full effect on HbA1c (<8 weeks). Many herbal remedies had not been evaluated in a meta-analysis. CONCLUSIONS: Several phytomedicines medicinal plants appear to be as effective as conventional antidiabetic treatments for reducing HbA1c. Rigorous trials with at least 3 months’ follow-up are needed to ascertain the effects of promising plant-based preparations on diabetes.